Risk factors, Clinical Features, Severity, Hematoma Characteristics and Etiological classification of Intracerebral Hemorrhage in Young Patients (18-49 Years) - Zannat, Tahira; Md Shahidullah; Md Rafiqul Islam; Md Al-Amin; Md Zamiur Rahaman; Shahida Bulbul; Belal Hossain (Bangladesh Journal of Neuroscience, 2026)
Background: Intracerebral hemorrhage (ICH) is the third common cause of all strokes but it is the deadliest subtype. ICH in younger adults is less frequent than in older people; however, it has more health and economic impact on individual, their family, and society. To ensure a favorable outcome, it is important to understand characteristics of ICH in young patients with factors contributing to its outcome. Our aim was to study the risk factors, etiologic distribution, clinical features, severity and hematoma characteristics of ICH in young patients. Objective: To evaluate the risk factors, etiologic distribution, clinical features, severity and hematoma characteristics of ICH in young patients. Methods: This cross sectional study was conducted with 100 patients of 18-49 years of CT or MRI proven ICH in Department of Neurology, Bangabandhu Sheikh Mujib Medical University and Stroke unit, National Institute of Neurosciences & Hospital, Dhaka from January 2020 to February 2022. The information about the demography, risk factors, clinical status, hematoma characteristics were noted at admission. The etiology of ICH was determined based on SMASH-U classification. Results: The mean age of patients was 39.54 years with 63% in 40-49 years group and 46 (46%) were female. Altered level of consciousness (61%) was the most frequent clinical presentation. Hypertension was the most common risk factor (64%). On admission, 24% patient had severe NIHSS (>20) with median NIHSS 15 and 18 %, 36%, 30%, 14%, 2% patients had ICH score 0, 1, 2, 3, 4 respectively. Thalamus and Basal Ganglia region (Deep) was the most common location of hematoma (69%). 45% patients had intraventricular hemorrhage and 24% and 29% had Midline shifting and hydrocephalus respectively. Mean hematoma volume was 17.11 ml. The etiological distribution according to SMASH-U classification showed most of the patients had hypertensive etiology (53%). Structural etiology accounts for 28% of the patients. 12% patient was of undetermined etiology. Among the structural causes 13% patients had aneurysm, 10% patients had AVM, 3% had Moyamoya disease, 1% had AVF and 1% had cavernoma. Conclusion: With the rising trend of hypertension in young age the etiological distribution of ICH in young is also changing, hypertension being the most frequent one. The severity of ICH in young tends to less severe.